Exploring academic performance among gifted and talented students: a comprehensive review - Razali, Fazilah; Abdul Majid, Noraziela; Mohd Azrin, Aleeya Adriana; Quah, Wei Boon (Human Resources Management Academic Research Society (HRMARS), 2024)
This study presents a Systematic Literature Review (SLR) conducted in accordance with established guidelines, employing PRISMA 2020 to scrutinize 16 carefully chosen research journals based on relevant keywords. The research scope focused on understanding the intricate factors contributing to sub-excellence among gifted students. The selected journal publications span the years 2016 to 2022, ensuring an up-to-date overview of the scholarly landscape. Our meticulous analysis encompassed methodology design, research focus, and experimental findings. The systematic review analysis reveals that several key factors significantly influence academic excellence in gifted students, prominently including motivation, emotional well-being, and students' perspectives on their educational experiences. Moreover, individual factors emerge as pivotal elements in enhancing excellence among this cohort, comprising self-regulation, goal assessment, academic self perception, academic self-concept, learning goal orientation, resilience, self-efficacy, task meaningfulness, negative self-concept, learning motivation, personal identity, and psycho motor skills.The outcomes of this study provide comprehensive insights that offer new dimensions, particularly in the context of teaching and learning for gifted students in Malaysia.